Desenvolvimento de um programa computacional em Scilab® baseado no método Pinch de integração energética - Resende, Marina Garcia (2013)
The increasing concern about environmental impacts caused by human activities has led scientists to look for ways to settle the situation. As regards chemical industries, one of the main focuses of this concern is the energy saving. Over several studies down the years, the idea of Pinch technology has risen up as one of the main and most efficient techniques of energy integration so far. It is based on the division of the problem into two systems starting from Pinch point, in which retrofits and/or synthesis of heat exchanger networks are realized separately, grounded on Thermodynamics principles. Nevertheless, at times, the calculation needed for this methodology can be tedious and time consuming. For that effect, there is the need to use software s to execute faster the initial calculations that Pinch method demands, in order to make it easier the future project of heat exchanger networks. The purpose of this work was to create a computer program in Scilab® language, for application of basic principles of Pinch analysis. Five case studies were presented to illustrate and test the performance of the new program. Furthermore, some of the main properties of this technique are presented, proving to be very interesting and inspiring for the rising or new researches in the area. From this work, it can be concluded that Pinch analysis is a relatively simple and efficient way to the retrofit and synthesis of heat exchanger networks, being able to be used in the solution of a several range of problems. Thus, energy savings associated to capital savings are possible, making it easier to exist a quality deal between the environment and profitability of chemical industries. Besides, the new program implemented in Scilab® has shown up to be a really efficient tool in the application of the method, facilitating the learning of users recent presented to Pinch technology and also being useful to more experienced designers, presenting satisfactory results regarding energy optimization of processes.